THE EFFECT OF PRODUCT REVIEWS, TRUST, AND PRICE ON PURCHASE DECISIONS IN THE TIKTOKSHOP MARKETPLACE ON MALIKUSSALEH UNIVERSITY STUDENTS - Rini Maulinda; Heriyana; Siti Maimunah; M. Subhan (RADJA PUBLIKA, 2024)
The purpose of this study was to determine how much influence product reviews, trust influence, price influence, on purchasing decisions in the TikTok marketplace. The method used is quantitative, the population is Malikussaleh University students from the 2018-2022 intake who have made purchasing decisions on TikTok, while the number of samples used is 174 respondents, so the data used is primary data from the results of the questionnaire, data analysis using multiple linear regression and hypothesis testing. The results of this study indicate that product reviews have a significant effect on purchasing decisions on TikTok, this is because the significance value is 4.180> 1.974. Trust has a significant effect on purchasing decisions on TikTok, this is because the significance value is 4.355> 1.974. Price has a significant effect on purchasing decisions on TikTok, this is because the significance value is -3.461 <-1.974. Product reviews, trust, and price have a significant effect on purchasing decisions, this is because the significance value is 67.173> 3.05.